THE EFFECT OF ADDITION CINNAMON LEAF EXTRACT IN FEED ON LIVER FAT CONTENTS AND HEALTH OF CATFISH - Rolin, Febrina; Setiawati, Mia; Jusadi, Dedi; Pangentasari, Dwinda; Arbajayanti, Rahma Dini (Jurnal Perikanan Unram, 2025)
Cinnamon leaves contain active compounds such as polyphenols and flavonoids which have antioxidant properties and play a role in lipid metabolism processes. This active substance is known to reduce liver fat levels and has the potential to increase the immune response in catfish. This research aims to determine the effect of adding cinnamon leaf extract to feed on liver fat levels and the health of catfish. Cinnamon leaf extract was added to the feed at five different doses, namely 0 g/kg (control), 0.5 g/kg, 1 g/kg, 2 g/kg, and 4 g/kg feed. The results of the study showed that the addition of cinnamon leaf extract to the feed reduced the fat content in the liver of catfish as seen from the decrease in fat degeneration in the liver of catfish compared to the control. Total erythrocytes, hemoglobin levels and hematocrit levels of fish treated with the addition of cinnamon leaf extract to the feed were lower and significantly different (P<0.05) compared to controls, but total leukocytes were not significantly different between treatment and control.